Invariance of an extended technology acceptance model across gender and age group - Tunku Ahmad, Tunku Badariah; Madarsha, Kamal Basha; Zainuddin, Ahmad Marzuki; Ismail, Nik Ahmad Hisham; Khairani, Ahmad Zamri; Nordin, Mohamad Sahari (David Publishing Company, 2011)
In this study, we examined the likelihood of a TAME (extended technology acceptance model), in which the interrelationships among computer self-efIicacy, perceived usefulness, intention to use and self-reported use of computer-mediated technology were tested. In addition, the gender- and age- invariant of its causal structure were evaluated. The data were collected from a self-reported questionnaire administered to 477 administrative staff of a public university in Malaysia. The results of structural equation modeling supported the adequacy of TAME. Although the TAME's causal structure was applicable to both male and female staff, age group appeared to moderate the structural relationships among the constructs of interest